Taximin, a conserved plant‐specific peptide is involved in the modulation of plant‐specialized metabolism. Issue 7 (23rd May 2014) - Onrubia, Miriam; Pollier, Jacob; Vanden Bossche, Robin; Goethals, Marc; Gevaert, Kris; Moyano, Elisabet; Vidal‐Limon, Heriberto; Cusidó, Rosa M.; Palazón, Javier; Goossens, Alain
Summary Small peptides play important roles in the signalling cascades that steer plant growth, development and defence, and often crosstalk with hormonal signalling. Thereby, they also modulate metabolism, including the production of bioactive molecules that are of high interest for human applications. Yew species (Taxus spp.) produce diterpenes such as the powerful anticancer agent paclitaxel, the biosynthesis of which can be stimulated by the hormone jasmonate, both in whole plants and cell suspension cultures. Here, we identified Taximin, as a gene encoding a hitherto unreported, plant‐specific, small, cysteine‐rich signalling peptide, through a transcriptome survey of jasmonate‐elicited T. baccata suspension cells grown in two‐media cultures. Taximin expression increased in a coordinated manner with that of paclitaxel biosynthesis genes. Tagged Taximin peptides were shown to enter the secretory system and localize to the plasma membrane. In agreement with this, the exogenous application of synthetic Taximin peptide variants could transiently modulate the biosynthesis of taxanes in T. baccata cell suspension cultures. Importantly, the Taximin peptide is widely conserved in the higher plant kingdom with a high degree of sequence conservation. Accordingly, Taximin overexpression could stimulate the production of nicotinic alkaloids in Nicotiana tabacum hairy root cultures in a synergistic manner with jasmonates. In contrast, no pronounced effects of Taximin overexpression on the specialized metabolism in Medicago truncatula roots were observed. This study increases our understanding of the regulation of Taxus diterpene biosynthesis in particular and plant metabolism in general. Ultimately, Taximin might increase the practical potential of metabolic engineering of medicinal plants.